Expediente / Masthead - Huff Júnior, Arnaldo Érico (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2013)
Expediente / Masthead<a style="text-decoration: none; color: #006699; font-family: 'Times New Roman', Times, Georgia, serif; font-size: medium; line-height: 22px;" href="http://www.hotfranquias.com.br/ideias-de-franquias-baratas-inovadoras/" target="_blank">